(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2024)
This paper provides a critical analysis of juvenile justice practices in Indonesia, with a focus on human rights issues related to the incarceration of children. Despite legal protections for minors under Indonesian law, including the Child Protection Law (2002), the reality for many children in the justice system is far from ideal. This research examines the treatment of children in detention, exploring issues such as overcrowding, lack of adequate rehabilitation programs, abuse, and the absence of proper legal representation. Using case studies from Indonesian youth detention centers, the paper analyzes how the criminal justice system fails to uphold international human rights standards, including the United Nations Convention on the Rights of the Child (CRC). Furthermore, the study explores the social and economic factors that contribute to the criminalization of children, such as poverty, lack of education, and the influence of gangs. The paper argues for urgent reforms in Indonesia’s juvenile justice system, calling for a shift toward rehabilitation, diversion programs, and the abolition of punitive practices. The findings highlight the need for better training of law enforcement and judicial officers, alongside increased public awareness of children’s rights.